Contemporary issues in business and financial management in Eastern Europe - Grima, Simon; Thalassinos, Eleftherios (Contemporary studies in economic and financial analysis, 2018)
This special 100th edition of the Emerald book series Contemporary Issues in Economic and Financial Analysis dedicates 14 chapters to contemporary issues in business and financial management in Eastern Europe by authors invited mainly from the Rostov State University of Economics. As the title suggests, the chapters are a mix of studies on economic and financial aspects in Eastern Europe. Two chapters are dedicated to the green economy and finance and others to information technology in banks and the treasury, problems of fund raising for accumulated damage repair, company business and individual entrepreneurship activity strategy, competency-based management, the economic coenosis theory, the fiscal mechanism, global interaction in the world economy, bank economic capital model, corporate reporting and the concept of alienation.